ANALISIS TINGKAT BRAND LOYALTY PENGGUNA JASA TRANSPORTASI BUS MAKMUR TRAYEK PEKANBARU - MEDAN - Elisabeth, Novita; Restuti, Sri; Musfar, Tengku Firli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This Research aim to know storey of brand loyalty service users of Makmur bus transportation route Pekanbaru - Medan. Research executed in Great Terminal Port Payung Sekaki ( TBRPS) Pekanbaru. This Population Research all service user of CV Makmur transportation. Prosperous route of Pekanbaru – Medan Class of AC-TOILET in the year 2014. Pursuant to from result of obtained calculation by using descriptive analysis, passing frequency distribution test that majority service user of Makmur Bus transportation Pekanbaru Route Pekanbaru – Medan have storey faithfulness of brand storey of Likes brand the among 5 level faithfulness of brand. Position faithfulness of customer storey of Likes brand the meaning service user of Makmur Bus transportation cutomer which seriously take a fancy to brand and have emotional binding with Prosperous brand. Cutomer residing in storey of loyalty this represent customer which must be defended and improved to be able to climb higher level again that is buyer committedKeywords: Brand Loyalty, Consumer, Service Transportation